The impact of rehabilitation programs on patients postoperative recovery after spine surgery - Muhammad Jehanzeb (Romanian Neurosurgery, 2024)
Spine surgery is a common intervention aimed at improving the lives of individuals with various spinal conditions, and the success of this procedure extends beyond the operating room to the postoperative recovery phase. This research paper explores the impact of rehabilitation programs on postoperative recovery in spine surgery patients. By delving into the multidisciplinary approach of rehabilitation, including physical therapy, occupational therapy, pain management, and patient education, the study aims to provide a comprehensive understanding of how these programs optimize outcomes and restore functional abilities.